2021
DOI: 10.1186/s12888-021-03567-7
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual dysphoric disorder and childhood maltreatment, adulthood stressful life events and depression among Lebanese university students: a structural equation modeling approach

Abstract: Background Premenstrual Syndrome (PMS) is a cyclic sequence of physical and behavioral symptoms that arise in the second half of the menstrual cycle. The extreme type of PMS is Premenstrual Dysphoric Disorder (PMDD). The current study aims at examining 1) the effects of childhood maltreatment and current life’s stressful events on PMDD, and 2) the mediating role of depression in these associations among Lebanese university female students. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The PMS was linked to psychological symptoms that ranged from irritability to depression and could depend on cultural perspectives and dealing with menstruation, social, environmental as well as hormonal changes [20][21][22]. Looking to the fact that stressful university study and great repressibilities that the students go through might increase and intensify the psychological symptoms out of the other PMS symptoms which was found in one study in Lebanon among university students [23]. In our study, we found that PMS symptoms were interfering the most with participants' daily routine work or school and relationships, similar to what ndings by Malki as among 274 females, aged from 18 to 57 years, having PMS interfering with their home responsibilities, relationships with their families, social life activities, and work productivity [24].…”
Section: Discussionmentioning
confidence: 99%
“…The PMS was linked to psychological symptoms that ranged from irritability to depression and could depend on cultural perspectives and dealing with menstruation, social, environmental as well as hormonal changes [20][21][22]. Looking to the fact that stressful university study and great repressibilities that the students go through might increase and intensify the psychological symptoms out of the other PMS symptoms which was found in one study in Lebanon among university students [23]. In our study, we found that PMS symptoms were interfering the most with participants' daily routine work or school and relationships, similar to what ndings by Malki as among 274 females, aged from 18 to 57 years, having PMS interfering with their home responsibilities, relationships with their families, social life activities, and work productivity [24].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies showed that the prevalence of PMS among Academics at a University in Midwest Brazil was 46.9% ( 38 ), and 21.1% for university students ( 39 ), which are higher than ever before. Moreover, risk factors for PMS/PMDD include childhood abuse and neglect ( 40 ), childhood maltreatment ( 41 ), and perinatal depression ( 42 ), among others.…”
Section: Discussionmentioning
confidence: 99%
“…The total score is calculated by summing the answers to the 17 items (range between 17 and 68). The Arabic version has been previously used [ 39 ]. In this study, the Cronbach’s alpha was 0.94.…”
Section: Methodsmentioning
confidence: 99%